The effect of Coronavirus Disease 2019 (Covid-19) towards consumer social well-being in Malaysia - Damin, Zahrul Akmal; Isa, Khairunesa; Saleh, Nor Shela; Abdullah, Muhaymin Hakim; Ramlan, Najah (Penerbit UTHM, 2021)
Responding to the unprecedented threat of Covid-19 to the life of all humanity, it were directly affect human mentally and physicaly. This outbreak consequences lead to human well-being being affected. To break this infection chain, the government has been announced to implement the Movement Control Order (MCO). This study try to identify the consumer social well-being during MCO and the impact of social well-being based on household income. A total of 340 consumers around Malaysia were randomly selected to participate in this survey. This survey used Flanagan Quality of Life Scale (1970) indicator to measure the consumer’s social well-being. The findings showed that the implementation of MCO made the aspect of consumers’ social well-being still in good condition because most respondents rated five (5) out of fifteen (15) items as mostly satisfied (scale 5) to their quality of time during the implementation of MCO. Meanwhile, household income did not affect the level of their social well-being because most of the respondents concerned more on human relationship rather than financial. Overall it can be said that human touch and the element of interaction between human have a significant impact to human social well-being.